Open-label phase 2 trial of first-line everolimus monotherapy in patients with papillary metastatic renal cell carcinoma: RAPTOR final analysis. (December 2016) - Escudier, Bernard; Molinie, Vincent; Bracarda, Sergio; Maroto, Pablo; Szczylik, Cezary; Nathan, Paul; Negrier, Sylvie; Weiss, Claudia; Porta, Camillo; Grünwald, Viktor; Albiges, Laurence
Abstract: Background: Papillary histology accounts for 10–15% of renal cell carcinoma (RCC), and treatment options for patients with this subtype are limited. The RAPTOR (RAD001 in Advanced Papillary Tumor Program in Europe;ClinicalTrials.gov, NCT00688753 ) study evaluated first-line everolimus in patients with papillary metastatic RCC (mRCC). Methods: This phase 2 trial enrolled previously untreated patients with type 1 or type 2 papillary mRCC. Papillary histology was confirmed by central review and was performed for every patient. Patients received oral everolimus 10 mg once daily until disease progression or unacceptable toxicity. The primary end-point was progression-free survival (PFS) rate at 6 months among the first 44 patients of the per protocol (PP) population. Secondary end-points included PFS, tumour response, overall survival (OS), and safety. Findings: Analysis sets included safety (N = 92; 100%), intent-to-treat (ITT) (n = 88), and PP populations (n = 46). In the safety population, most patients were men (78%) and the mean age was 60 years (range 23–84). Papillary histology was confirmed in 78% of patients (type 1, 32%; type 2, 64%; missing information, 4%). PFS rate at 6 months was 34% (80% confidence interval [CI] 25–45). In the ITT population, median PFS was 4.1 months (95% CI 3.6–5.5), 65% of patients achieved stable disease, and median OS was 21.4 months (95% CI 15.4–28.4). Among patients with type 1 or type 2 histology, median PFS was 7.9 months (95% CI 2.1–11.0) and 5.1 months (95% CI 3.3–5.5), respectively, and median OS was 28.0 months (95% CI 7.6–not estimable) and 24.2 months (95% CI 15.8–32.8), respectively. Common grade >2 adverse events were asthenia (13%), anaemia (7%), and fatigue (5%). Interpretation: Results of this large prospective study in papillary mRCC demonstrated that everolimus provides some clinical benefit to this patient population and highlight the need for central pathological review of this rare tumour.